Assessing current state and prospects for housing construction development in the Far Eastern Federal District of the Russian Federation - A. P. Alekseenko; I. A. Lavrentiev; N. Ye. Latysheva (Вестник университета)
Housing commissioning in the Far Eastern Federal District of the Russian Federation was low until 2019, which resulted in housing availability lower than the national average. The Government of the Russian Federation implemented the program on preferential mortgage lending “Far Eastern Mortgage” that led to an increase in the housing availability in apartment buildings in the macro-region, purchased on credit, while stimulating price growth at a rate outpacing the increase in household incomes. The purpose of the study is to develop proposals for improving measures to support the housing construction market of apartment buildings in the Far Eastern Federal District. The data on the volume and structure of multifamily housing under construction, the main factors of construction cost formation in the macro-region have been analyzed. The mechanism of mortgage influence with state support on the supply growth has been described. It is shown that the dynamics of supply is insufficient to achieve the average Russian values on housing provision of the population, in this connection stimulation measures require improvement. The high dependence of the housing market on mortgage lending programs with state support has been revealed. Based on the comparative analysis of the Far Eastern Mortgage program with other preferential mortgage programs, the article presents proposals for improving the measures of state support for multifamily housing construction in the Far East.